Predictors of non-response in a UK-wide cohort study of children's accelerometer-determined physical activity using postal methods. Issue 3 (1st March 2013) - Rich, Carly; Cortina-Borja, Mario; Dezateux, Carol; Geraci, Marco; Sera, Francesco; Calderwood, Lisa; Joshi, Heather; Griffiths, Lucy J
Abstract : Objectives: To investigate the biological, social, behavioural and environmental factors associated with non-consent, and non-return of reliable accelerometer data (≥2 days lasting ≥10 h/day), in a UK-wide postal study of children's activity. Design: Nationally representative prospective cohort study. Setting: Children born across the UK, between 2000 and 2002. Participants: 13 681 7 to 8-year-old singleton children who were invited to wear an accelerometer on their right hip for 7 consecutive days. Consenting families were posted an Actigraph GT1M accelerometer and asked to return it by post. Primary outcome measures: Study consent and reliable accelerometer data acquisition. Results: Consent was obtained for 12 872 (94.5%) interviewed singletons, of whom 6497 (50.5%) returned reliable accelerometer data. Consent was less likely for children with a limiting illness or disability, children who did not have people smoking near them, children who had access to a garden, and those who lived in Northern Ireland. From those who consented, reliable accelerometer data were less likely to be acquired from children who: were boys; overweight/obese; of white, mixed or 'other' ethnicity; had an illness or disability limiting daily activity; whose mothers did not have a degree; who lived in rented accommodation; who exercised once a week or less; who had been breastfed; were from disadvantaged wards; had younger mothers or lone mothers; or were from households with just one, or more than three children. Conclusions: Studies need to encourage consent and reliable data return in the wide range of groups we have identified to improve response and reduce non-response bias. Additional efforts targeted at such children should increase study consent and data acquisition while also reducing non-response bias. Adjustment must be made for missing data that account for missing data as a non-random event.